Study on the sequence activities of the 2021 Yangbi MS 6.4 earthquake in Yunnan - Li, Xiaohan; Zheng, Jianchang; Zhang, Haijiang; Cui, Huawei; Li, Cuiqin (Frontiers in Earth Science, 2023)
On May 21, 2021, the MS 6.4 earthquake struck Yangbi County, Dali City, Yunnan Province. Minor seismic activities were common both before and after the earthquake; the foreshock sequence activity characteristics of this earthquake were studied to gain a better understanding and more perspective. First, between May 18 and July 5, 2021, we collected data of the seismic events from the Yangbi MS 6.4 earthquake sequence, filtered out the more complete earthquake sequences, and performed double-difference earthquake relocation. Then, we improved the nearest-neighbor distance algorithm and used it in conjunction with the Gaussian mixed model fitting method to conduct a comprehensive multiple factor analysis of the Yangbi MS 6.4 earthquake sequence. The main findings of our preliminary analysis are as follows: 1) We distinguished the foreshocks, mainshocks, and aftershocks of the Yangbi earthquake sequence as well as their higher-order aftershocks, using the method described in this paper, and we can obtain clear intergenerational relationships between them. We identified eight "foreshocks" with statistically greater physical significance than the others. 2) We found that the b-value of the Yangbi foreshock sequence was clearly on the lower end of the spectrum, with an obvious nonlinear amplification process, and can be divided into three foreshock subsequences: subsequence I with the lowest b-value and a concentrated spatial distribution, which is an F-value foreshock sequence; subsequence II with an overall shallower source depth and an obvious rebound in b-value, which is an explosive aftershock sequence; subsequence III with a lower b-value and a rapid rupture spread, which is a typical U-F-ρ foreshock. 3) We constructed a topological tree of the Yangbi foreshock sequence in Yunnan Province and analyzed the distribution and topology of the three subsequences (combined) of the Yangbi MS 6.4 foreshock sequence and found the following: the topology of subsequence I was more linear than the sequence II, and its rupture mode was similar to the fluid intrusion rupture in a specific channel; sequence II independently formed a main-aftershock mini-sequence, probably triggered by its shallow brittle rupture, which caused the fluid intrusion rupture to spread faster and eventually triggered the Yangbi MS6.4 mainshock.